Hubungan Peran Perawat Dengan Diet Makanan Pada Pasien Artritis Gout Di Posyandu Lansia Dusun Joho Desa Pasirian - Hariyanto Hariyanto; Nafolion Nur Rahmat; Sunanto Sunanto (STIKes Ibnu Sina Ajibarang, 2023)
Gout arthritis is a disease in which excess gout accumulates in the body, either due to increased production, decreased elimination through the kidneys or due to increased intake of foods high in purines. The aim of this study was to analyze the relationship between the role of nurses and diet in gouty arthritis patients.The research design used iscross sectional. The sampling technique used ispurposive sampling. The data was taken at the elderly Posyandu, Dusun Joho, Pasirian Village, with the instrument used, namely a questionnaire. The total population is 40 elderly with a selected sample of 30 respondents.The results of the study showed that nurses carried out their role sufficiently, amounting to 18 respondents (60%). Meanwhile, the majority of respondents had sufficient dietary behavior, amounting to 15 respondents (50%). Based on the Spearman rank test, a probability value or p value of 0.032 is less than the standard significant p value of 0.05, which means that there is a relationship between the nurse's role and diet in Gout Arthritis patients at the Elderly Posyandu.It is expected that nurses or other health workers will be more active in carrying out their roles as nurses, namely educators, coordinators, advocates, nursing care providers, and collaborators in carrying out discharge planning in gout arthritis patients in improving the food diet in gout arthritis patients. . Keywords : Nurse's Role, Food Diet, Gouty Arthritis